The Effect of Discovery Learning on 21st Century Skills for Elementary School Students (Universitas Negeri Semarang, 2020)
21st century needs human resources that have an adequate ability to face the global era. This ability can trained at the education stage by using a good method in learning, discovery learning can be choices to release that. This study's aim is to analyze the effect of learning with discovery models on 21st-century skills for elementary school students. This study uses experimental research. Experimental research method is a research conducted on variables for which data are not yet available that it needs to be manipulated through the treatment of research subjects in which the impact is measured. Results of the creative thinking skills gain test showed the average value of the experimental class was 0.72 while the average value of the control class was 0,39. This shows the discovery model gives more influence on the student’s skills to think creatively. Results of the critical thinking skills gain test showed the average value of the experimental class was 0.78 while the average value of the control class was 0.60. This shows the discovery model gives more influence on the student’s skills to think critically. The results of communication skills test showed a significance value of 0.82. This value is higher than 0.05, it means that students communication skills with the discovery model are not higher than group of students that learning with the expository model. The result of collaboration skills showed a significance value of 0.91. This value is greater than 0.05, it’s means that the collaboration skills of students with discovery models are not higher than those of students who learn with expository models. This research is expected to be a reference for teachers in using learning models when teaching.